The Effect of Low Vs Standard Pneumoperitoneum Pressure during Laparoscopic Hysterectomy - Iftikhar, Mahrukh; Bano, Alia; Saleem, Samina; Ayub, Bushra (Indus Journal of Bioscience Research, 2025)
Background: Laparoscopic hysterectomy, the minimally invasive procedure, relies heavily on pneumoperitoneum pressure for both surgical safety and vision. Objective: To compare the effects of low pneumoperitoneum pressure (12 mmHg) versus standard pressure (15 mmHg) during laparoscopic hysterectomy in terms of operative outcomes. Methodology: This randomized controlled trial was conducted at the Department of Gynaecology and Obstetrics, Patel Hospital, Karachi, from January to December 2024. The low-pressure (n=28) and standard-pressure (n=28) groups were randomly allocated to 56 women who were scheduled for laparoscopic hysterectomy for benign causes. Following established operating procedures, skilled laparoscopic gynecologists operated on both groups. The length of the procedure, the amount of CO₂ insufflated, the predicted blood loss, and the length of hospital stay were among the important intraoperative characteristics that were noted. SPSS version 20.0 was used to analyze the data using the proper statistical tests; p<0.05 was deemed significant. Results: The low-pressure group's median operation time was 95 minutes (IQR: 75–120), whereas the standard-pressure groups were 100 minutes (IQR: 75–120) (p=0.954). In the low-pressure group, the median amount of CO₂ insufflated was 335 liters (IQR: 279–535), whereas in the normal group, it was 410 liters (IQR: 290–520) (p=0.577). 26 patients (92.9%) in both groups had an estimated blood loss of less than 50 ml, whereas 2 patients (7.1%) in each group had an estimated blood loss of more than 50 ml (p=1.000). Both groups' median hospital stays lasted two days (IQR: two to three vs. two to two; p=0.195). In both groups, pelvic visualization was generally assessed as "good." Conclusion: Low pneumoperitoneum pressure (12 mmHg) is a safe and effective alternative to standard pressure in laparoscopic hysterectomy without compromising surgical outcomes.